Public Health Surveillance for the Prevention of Pesticide-Related Illness in Illinois. Issue 5 (May 2020) - Kyeremateng-Amoah, Emmanuel; Friedman, Lee; Wahl, Michael; Forst, Linda
Abstract : Objectives: There is no pesticide related illness (PRI) surveillance program in Illinois. This study examines the quality of state-based data sources for their ability to inform public health surveillance on PRI. Methods: We estimated the counts of PRI by probabilistic data linkage of hospital discharge, emergency department, and poison center databases from 2010 to 2015. We characterized identified PRI cases. Results: We identified 3867 unique cases of PRI and 6269 asymptomatic pesticide exposures. Out of the 3867 PRI cases, there were 1319 emergency department visits and 321 hospitalizations. We identified 13 deaths and 1640 major or moderate effects from PRI. Over half of ingestion related exposures occurred in children aged 0 to 4 years. Workers' compensation and Emergency Medical Service data were unusable. Conclusion: An effective public health surveillance on PRI requires reliable state data sources and cost-effective methods of assembling data from multiple sources. Abstract : Supplemental Digital Content is available in the text